SEMANTIChESKIE OSOBENNOSTI Tsvetovoy LexiconV RUSSKOM I UZBEKSKOM Yazykakh (Universal International Scientific Journal, 2026)
This paper examines the semantic dynamics of color-denoting vocabulary in the Russian and Uzbek languages ​​from a comparative perspective.The development of color term meanings is analyzed, including the processes of semantic expansion, metaphorization, and the formation of symbolic interpretations. The study's material includes data from modern explanatory and phraseological dictionaries, as well as examples from literary and journalistic texts. The study utilizes methods of comparative and cognitive-semantic analysis. The results show that the basic meanings of color terms in both languages ​​are universal, while their secondary meanings are distinctly culturally specific. In Russian, color-denoting vocabulary is more often used to express emotional and evaluative characteristics, while in Uzbek, the symbolic function of color terms, linked to traditional cultural beliefs, is strengthened. The obtained results confirm the importance of a linguacultural approach to studying the semantics of color-denoting vocabulary.
Keywords: Color-denoting vocabulary; Semantic dynamics; Russian language